2000
DOI: 10.1136/aim.18.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Myofascial Trigger Points: Pathophysiology and Correlation with Acupuncture Points

Abstract: SummaryA review is made of recent studies on myofascial trigger points (MTrP) and their mechanism is discussed. Clinical and basic science studies have shown that there are multiple MTrP loci in a MTrP region. A MTrP locus contains a sensory component (sensitive locus) and a motor component (active locus). A sensitive locus is a point from which tenderness or pain, referred pain, and local twitch response can be elicited by mechanical stimulation. Sensitive loci (probably sensitised nociceptors) are widely dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 52 publications
0
70
0
2
Order By: Relevance
“…Since there is scientifi c evidence supporting a link between electrical stimulation of acupuncture points and the release of endorphins, these researchers also theorised that electro-acupuncture could activate the body's pain relief system, increasing the concentration of endorphins in the central nervous system and decreasing the amount of pain signals that arrive at the spinal cord level. (30,31) The present study was not without limitations. As a single author performed this review, the possibility of bias in study selection and appraisal, which could have impacted its results, cannot be disregarded.…”
Section: Discussionmentioning
confidence: 99%
“…Since there is scientifi c evidence supporting a link between electrical stimulation of acupuncture points and the release of endorphins, these researchers also theorised that electro-acupuncture could activate the body's pain relief system, increasing the concentration of endorphins in the central nervous system and decreasing the amount of pain signals that arrive at the spinal cord level. (30,31) The present study was not without limitations. As a single author performed this review, the possibility of bias in study selection and appraisal, which could have impacted its results, cannot be disregarded.…”
Section: Discussionmentioning
confidence: 99%
“…Hong, Audette and Blinder suggested that acupuncturists may well be treating trigger points whenever they are treating ahshi points. 270,271 While some believe that trigger points are nearly always acupuncture points especially in pain management, [272][273][274][275] well-known acupuncturist…”
Section: Dry Needling and Acupuncturementioning
confidence: 99%
“…15 The acupuncture or dry needling of a myofascial trigger point appears to provide immediate relief of pain. It is obvious that a trigger point is different from a tender point or some acupuncture points.…”
Section: Figure 3 Effect Of Acupuncture On Chronic Low Back Pain By Vmentioning
confidence: 99%